Effect of Metacognition and Learning Style on Academic achievement of college Students - Hossain, Kazi Masud; Patra, Anujit; Divyagunananda, Swami (Papanda Publisher, 2025)
Metacognition and learning styles play a crucial role in shaping academic achievement. This study investigates the connection between these factors and their impact on students' academic performance. This research seeks to identify the connections between metacognition, learning styles, and academic achievement and to ascertain whether or not these elements significantly impact students' performance. A descriptive survey design was adopted, and 270 undergraduate humanities and science students from Hooghly district colleges in West Bengal, India, were selected. The Metacognitive Inventory (MCI) and the Learning Style Inventory (LSI) questionnaires were used for data collection. Pearson's Product Moment Correlation and multiple regression analysis were conducted to analyze the data. The study's results depict strong positive relations between metacognition and academic performance, learning styles and academic performance, and metacognition and learning styles. The research concludes that both metacognition and learning styles have a general impact on academic performance, implying that students with greater awareness of metacognition and responsive learning styles would perform better at college.